Bio-templated synthesis of hierarchically ordered macro-mesoporous anatase titanium dioxide flakes with high photocatalytic activity. Issue 20 (6th March 2015) - Li, Bing; Zhao, Jianquan; Liu, Jing; Shen, Xinyu; Mo, Shaobo; Tong, Hua
<x xml:space="preserve">Abstract</x> Hierarchically ordered macro-mesoporous anatase TiO2 flakes were synthesized by using rose petals and P123 as dual templates with high photocatalytic activity.